Role of Transfusion Medicine Specialist in Stem Cell Transplant: Experience in Bangladesh - Afroz, Tamanna; Saleh, Abu Jafar Mohammed (Pulse, 2024)
Over the years, the field that was once known as blood banking has evolved into the discipline of Transfusion Medicine. Transfusion Medicine has become a broad, multidisciplinary field which include various facets of clinical medicine. Transfusion medicine specialist plays a vital role in the supportive care of patients undergoing stem cell transplantation, with a spectrum of applications including peripheral blood stem cell collection, graft manipulation, cryopreservation, donor lymphocyte infusions and evaluation of immunohematological issues in ABO and RhD mismatched and other transplant situations. Pulse Vol.15, 2023 P: 34-37